MEMAHAMI KABAR SEJARAH DAN PERIODE DEMOKRASI DI INDONESIA - Yeyen Subandi (Dauliyah Journal of Islamic and International Affairs, 2017)
“Democracy is; when the majority vote more mainstream, and more important than truth of the word of God “. Democracy is a political process that not only promote or rely on what was a policy, the policy is not only supporting the political process in a democracy, but the policy could be a boomerang on democracy. Not necessarily people know, nor understand what democracy is, and also after the process was whether the majority of the people agree with democracy, although the notion of democracy is government by and for the people. Or most people are forced to accept democracy. Indeed, the idea of democracy that was born of the human mind, which at the time was not satisfied with the system at the time imperliasme theotracy western, democratic system that all countries are proud of the fact that the system has only transferred power from the hands of the church into the hands of the capitalist, not to the people. And very reasonable at all in fact when democracy remain state hands, not in the hands of the people, because we presume, are the state church, church is the master, and this process is not widely known by the public (us) as citizens. And in the 15th century also the creed of secularism was born.